Is the Airline Trustworthy? The Impact of Source Credibility on Voluntary Carbon Offsetting. (May 2019) - Zhang, Beile; Ritchie, Brent; Mair, Judith; Driml, Sally
Airlines have introduced voluntary carbon offsetting (VCO) products to encourage consumers to mitigate emissions from their air travel. However, literature has suggested a low VCO adoption partly because of low perceived credibility. This study investigates the impact of source credibility (expertise and trustworthiness) on air travelers' purchase intention for aviation VCO products. This is the first study to conceptualize and test the influence of source credibility on air travelers' carbon offsetting behavior using communication theory. Source credibility of a message directly influences air travelers' purchase intention of aviation VCO products in a positive way. Examining source credibility components shows that trustworthiness has a significant positive impact on purchase intention, while the impact of expertise is not significant. Theoretical and practical implications of the findings are discussed, which highlight the importance of improving source credibility, and trustworthiness in particular, to encourage consumers to mitigate air travel emissions.